Croton bacupariensis (Euphorbiaceae), a new species from the Coastal Plain of Rio Grande do Sul, Brazil - Valduga, Eduardo; Cordeiro, Inês; Iganci, João Ricardo Vieira (Phytotaxa, 2021)
Croton bacupariensis, an endemic species from the coastal plain of the State of Rio Grande do Sul, southern Brazil, is described and illustrated. The new species shares morphological features with Croton gnaphalii, but differs mainly by the habit, indumentum of leaves and morphology of pistillate flowers. In addition; C. gnaphalii occurs all over the Pampa’s grasslands of Argentina, Uruguay and Rio Grande do Sul.